Competitive Strategy Analysis using SWOT and QSPM Matrix: A Case Study on MSMEs Putri Tunggal, Cikurubuk Main Market, Tasikmalaya - Sulistiawati, Nita; Madyasari, Rina (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the competitive strategies of Putri Tunggal MSMEs, a vegetable trading business in the Cikurubuk Main Market, Tasikmalaya, using SWOT and QSPM analysis. A qualitative descriptive approach was applied with purposive sampling of five informants consisting of the business owner, two employees, and two regular customers. Data were collected through in-depth interviews, direct observations, and documentation, then validated through source triangulation to ensure the validity and reliability of the findings.The SWOT analysis identified four strengths, namely product freshness based on direct procurement from farmers, competitive selling prices, friendly and responsive service, and a strong loyal customer base. Four weaknesses were also identified, including stock instability, limited financial recording, absence of formal business legality (NIB), and limited stall conditions. Four opportunities were found, consisting of consistently high demand for fresh vegetables, wholesale market expansion, government support programs for MSMEs, and potential product variations. Four threats were also identified, namely intense price competition, supply instability from farmers, the entry of new competitors, and unpredictable vegetable price fluctuations.The SWOT matrix generated eleven strategy alternatives, which were then evaluated using QSPM analysis to select five priority strategies. The top priority is wholesale segment development (TAS 6.40), followed by product variation addition (TAS 5.87), differentiation through freshness and premium service guarantees (TAS 5.82), scheduled procurement agreements with farmers (TAS 5.68), and NIB management with digital record-keeping (TAS 4.46). These strategic recommendations offer practical guidance for vegetable traders in traditional markets facing intense competition.